Wojna. Fiodor Martens i konferencja brukselska z 1874 roku - Tagirov, Arsen (PRAWO i WIĘŹ, 2025)
The article focuses on the role of Fyodor Martens in the 1874 Brussels Conference – the first international attempt to codify the laws and customs of war. Its aim is to highlight Fyodor Martens’ contribution to the development of international humanitarian law and to examine the political context and outcomes of the conference. Special attention is given to Fyodor Martens’ views on war, which he regarded as historically inevitable but in need of legal and moral limitation. The study analyzes the Russian draft convention, the positions of other participating states, and the broader impact of the Brussels Declaration. Although never ratified, the Declaration laid the foundation for later Hague Conventions and contributed significantly to the humanization of armed conflict.